GAMBARAN KADAR HEMOGLOBIN DAN INDEKS ERITROSIT PADA PASIEN TUBERKULOSIS PARU DI RSUD DR. M. HAULUSSY AMBON PERIODE JANUARI 2017 – APRIL 2018 - Reinhard Wilson Talakua; Vina Z. Latuconsina; Siti Hadjar Malawat (PAMERI, 2020)
Pulmonary tuberculosis (TB) is an infection disease caused by Mycobacterium tuberculosis. Pulmonary TB remain a major health problem and the most common cause of death in the world especially in developing countries. Pulmonary TB infection could cause clinical manifestation, which is haematology disorders like anemia. Many studies has reported anemia as a common complication in patients with pulmonary TB. This research aims to determine haemoglobin levels and erythrocytes index of patients with pulmonary TB at RSUD Dr. M. Haulussy Ambon in the periods from January 2017 - April 2018. This research uses a descriptive study by using medical records of patients with pulmonary TB. Among 65 patients with pulmonary TB, number of patients with anemia are 44 cases (67,7%) and 21 cases (32,3%) are not anemia. Pulmonary TB with anemia most suffered by male as much 24 cases (72,7%). The age group suffered most is 18 - 30 years old as much 23 cases (69,7%), but the age group suffered most according to percentage is 51 - 60 years old as much 80%. The most common types of anemia is hipocromic micrositer as much 23 cases (52,3%). Haemoglobin levels in patients with pulmonary TB are found most below the normal value or anemia and the most common types of anemia is hipocromic micrositer. Needs to be done more research on the analysis of the relation between anemia with pulmonary TB.